Post-Exercise Hypotension in Brazilian Jiu-Jitsu - Herrera-Valenzuela, T (Montenegrin Sports Academy, 2021)
Hypertension is a leading preventable cause of morbidity and mortality worldwide. Exercise is a widely recommended treatment strategy that has been shown to cause both acute and chronic reductions in blood pressure. This study aimed to explore the potential therapeutic effects of Brazilian jiu-jitsu training by assessing blood pressure responses during and after technical sparring. Seven Brazilian jiu-jitsu practitioners (age: 24.0±3.5 years; height: 1.75±0.02 m; body mass: 76.0±4.2 kg; BMI: 24.5±0.9) were included in the study. The participants performed three five-minute technical sparring rounds. Auscultatory measurements of blood pressure were obtained at rest, one minute post-sparring, and every ten minutes for a total of 60 minutes of recovery time. Between rounds, acute increases in both systolic blood pressure (p<0.0001) and diastolic blood pressure (p<0.0001) were observed. In the subsequent recovery period, both systolic blood pressure and diastolic blood pressure increased at the ten-minute mark compared to baseline values, but then started to gradually decline, with systolic blood pressure dropping 10.0±4.1 (p<0.0001) and diastolic blood pressure 5.0±4.1 mmHg (p=0.001) after one hour of recovery. These findings indicate that technical Brazilian jiu-jitsu sparring induces significant post-exercise decreases in blood pressure and thus may have value as a non-pharmacological treatment strategy for the prevention and management of hypertension. © 2021 Montenegrin Sports Academy. All rights reserved.